Pengaruh Daya Tarik Wisata dan Fasilitas Terhadap Kepuasan Pengunjung di Objek Wisata Pantai Tanjung Kelayang Kabupaten Belitung - Safari, Apay; Riyanti, Anti; Natasya, Firna (Manajemen dan Pariwisata, 2025)
This research is motivated by issues related to "The Influence of Tourist Attractions and Facilities on Visitor Satisfaction at Tanjung Kelayang Beach Tourist Object, Belitung Regency." This research aims to determine the extent of the influence of tourist attractions and facilities on visitor satisfaction at the tourist site. This study uses a quantitative approach with descriptive analysis and verificative analysis, employing a multiple linear regression analysis model. The sample used consisted of 100 respondents, namely tourists who visited Tanjung Kelayang Beach. Data management was conducted using SPSS 24 software. Based on the results of the instrument testing, it is declared valid with a value above 0.30 and reliable with a value above 0.70. The results of the descriptive analysis test showed that the value of the tourism attraction variable with an average of 4.14 falls into the "Good" category, the value of the facilities variable with an average of 4.16 falls into the "Good" category, and the value of the visitor satisfaction variable with an average of 4.20 falls into the "Very Good" category. Meanwhile, the results of the verificative analysis show that the coefficient of determination is 75.6%, with the remaining 24.4% being variables not examined in this study. The tourism attraction variable has a significance level of 0.000<0.05 and the facilities variable has a significance level of 0.003<0.05. The test results indicate that this study has a positive and significant impact between the tourist attraction variable and facilities on visitor satisfaction.